Goldilocks breaks in - Holub, Joan (New York: Scholastic Inc., 2015)
Goldilocks spies on the organization E.V.I.L.
5.9
3-6
760L
Keywords: Three bears (Tale) -- Juvenile fiction; Three bears (Tale) -- Fiction; Spies -- Fiction; Fantasy; Spy stories; Fantasy fiction